Quantifying particulate matter emission rates from naturally ventilated dairy buildings by considering roof opening contributions - Yujian Lu; Xiao Yang; Pan Xiao; Lei E; Chaoyuan Wang; Jing Yu; Chao Liang; Zhiwei Fang; Yongzhen Li (Atmospheric Environment: X)
Roof openings are typically fitted to naturally ventilated dairy building (NVDB) for better ventilation but their impact on air pollutant emission calculations has not been fully considered. Particulate matter (PM) emission rate (ER) for NVDB rely on the total ventilation rate (VR), outdoor PM concentration and average indoor PM concentration sampled either under the roof (Roof Sampling) or in the cubicle area (Cubicle Sampling), which may show large deviations due to its spatiotemporal variation of PM concentrations and complex airflow patterns. This study utilised a novel ER calculation method (Joint Sampling) that computes the respective emission from the roof and sidewall openings by matching each outlet's VR and PM concentration. By year-round field measurements of PM2.5 and the total suspended particulates (TSP), results showed that annual average ERs of PM2.5 and TSP were 10.8 mg h−1 cow−1 and 45.7 mg h−1 cow−1 for Roof Sampling, 12.7 mg h−1 cow−1 and 40.7 mg h−1 cow−1 for Cubicle Sampling, and 11.7 mg h−1 cow−1 and 45.9 mg h−1 cow−1 for Joint Sampling. Considering the Joint Sampling results were relatively true, Roof Sampling exhibited a maximum underestimate of PM2.5 emissions of 20.8% when sidewall curtains were fully opened, whilst Cubicle Sampling demonstrated a maximum overestimate of TSP of 10.2% when the aperture was closed. Using Joint Sampling, the roof opening contributed 39.3% and 24.4% of the annual PM2.5 and TSP emissions. When sidewall openings are partially or fully closed, the Joint Sampling calculation is preferable to estimate the ER of PM.